Implementasi Jaringan Komputer Diskless Dengan Menggunakan Mikrotik dan CCBoot - mahmud, mahmud (Sekolah Tinggi Manajemen Informatika dan Komputer PalComTech, 2020)
In teaching and learning activities, the provision of learning facilities is an important factor in improving the quality of the teaching and learning process between students and educators. The use of technology in the form of computers is an important means of improving the quality of the teaching and learning process. STMIK PalComTech is one of the private universities in the city of Palembang under the auspices of Kopertis Region II, which is located at Jalan Basuki Rahmat No. 05. STMIK PalComTech itself is a university in the field of computers and has a number of computer laboratories that are used to support teaching and learning activities. STMIK PalComTech has 3 computer labs, currently the STMIK PalComTech computer laboratory uses the concept of a stand-alone computer (Stand Alone) with each computer connected to a computer network that is joined to a public hotspot. This computer laboratory is used in addition to teaching and learning activities, it is also used for research activities, student activities and so on by students, educators, and even employees of STMIK PalComTech. In the process of using a computer laboratory, there are several problems, such as the slow and long process of starting an operating system, cumbersome and time consuming software maintenance and installation, and poor connection to the internet. In the process of solving these constraints, a technology that can overcome these problems is needed, and is also supported by an adequate computer network infrastructure. In this research, there will be a change in the concept of computers in the laboratory from being originally a stand-alone computer to a diskless-based computer (without independent storage media) or in other words, data storage is done centrally, namely on the server. The implementation of this research aims to increase the comfort in using computer laboratories to improve the quality of the teaching and learning process carried out at STMIK PalComTech.